2017
DOI: 10.47102/annals-acadmedsg.v46n6p217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Proportion and Healthcare Utilisation of Adult Patients with Uncontrolled Severe Asthma versus Non-Severe Asthma Seen in a Southeast Asian Hospital-Based Respiratory Specialist Clinic

Abstract: Introduction: Understanding the burden of uncontrolled severe asthma is essential for disease-targeted healthcare planning. There is a scarcity of data regarding the proportion, healthcare utilisation and costs of patients with uncontrolled severe asthma in Asia. This study aimed to plug the knowledge gap in this area. Materials and Methods: Consecutive patients with asthma managed in our respiratory specialist clinic were evaluated prospectively. Healthcare utilisation comprising unscheduled asthma-related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Even in fully adjusted models, people with mild and moderate-to-severe asthma were estimated to experience a rate of 2.7 and 6.2 times more respiratory hospital admissions compared with those without asthma, respectively. Our results show that asthma burdens secondary care with significantly higher rates of hospital admissions, length of stay and hospital costs compared with the asthma-free population, with more severe disease contributing disproportionately to this burden, mirroring the findings of other studies within the asthma literature 25–28. It is likely, however, that the fully adjusted models in this study underestimate the full effect of asthma on hospital outcomes, since socioeconomic deprivation, smoking, BMI and the comorbidities included here are highly associated with asthma 29.…”
Section: Discussionsupporting
confidence: 75%
“…Even in fully adjusted models, people with mild and moderate-to-severe asthma were estimated to experience a rate of 2.7 and 6.2 times more respiratory hospital admissions compared with those without asthma, respectively. Our results show that asthma burdens secondary care with significantly higher rates of hospital admissions, length of stay and hospital costs compared with the asthma-free population, with more severe disease contributing disproportionately to this burden, mirroring the findings of other studies within the asthma literature 25–28. It is likely, however, that the fully adjusted models in this study underestimate the full effect of asthma on hospital outcomes, since socioeconomic deprivation, smoking, BMI and the comorbidities included here are highly associated with asthma 29.…”
Section: Discussionsupporting
confidence: 75%
“…This indicates that it is difficult to avoid hospital admissions in this group even with regular check-ups and a higher use of asthma medication. Adult patients with asthma have shown that greater utilization rates of asthma medications and health care services are associated with uncontrolled and severe asthma 16,17 . Furthermore, increased disease severity is associated with higher exacerbation frequency, emergency department visits, and hospital admissions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients with asthma have shown that greater utilization rates of asthma medications and health care services are associated with uncontrolled and severe asthma. 16,17 Furthermore, increased disease severity is associated with higher exacerbation frequency, emergency department visits, and hospital admissions. 18 This suggests that children with AD might have an increased risk of uncontrolled asthma or increased asthma severity compared with children without this comorbidity; however, asthma severity was not directly measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Three out of ten patients reported not having used any healthcare resource in the year prior to the study, and a considerable proportion of patients (40.8%) did not attend to any routine medical appointment in the same period, which goes against the asthma management recommendations that advocate each patient should have an asthma review at least once a year. 27 Unscheduled medical appointments, [28][29][30] Emergency Department visits (particularly among non-OCS users), 28,30,31 and hospitalizations 29,30,32 were also less frequent than reported by other studies. In fact, only 18% of the participants visited the ED due to asthma in the previous year, a lower proportion than that reported by step 3+ patients using a short-acting beta agonist (SABA) inhaler (45%) in a previous study conducted in Portugal.…”
Section: Discussionmentioning
confidence: 98%